Research progress on the synthesis of energetic N-oxides based on diazine, triazine and tetrazine - Jiarong Zhang; Huan Huo; Lianjie Zhai; Fuqiang Bi; Bozhou Wang (FirePhysChem, 2025)
The skeleton structures of azine (including diazine, triazine and tetrazine) are widely used as important candidate for building good performance energetic materials due to their uniform electron distribution, planar aromaticity, multi reactive sites and low ring tension. Introducing N-oxide coordination bonds into azine framework turns out to be an important and highly rewarding protocol for the construction of energetic compounds with balanced performances. A variety of energetic compounds with good comprehensive performances have been designed and synthesized by introducing NO coordination bonds to azine skeletons. In this work, a review of recent research in the synthesis and physicochemical properties of N-oxides energetic compounds based on diazine, triazine and tetrazine skeleton is presented. And the application research progress of typical N-oxides energetic compounds are introduced.